FM14 Session 3: The IAU National Outreach Coordinators (NOCs) Network – Coordinating and Catalyzing Astronomy Outreach Worldwide. Issue Volume 14:Issue A30(2018) (August 2018) - Cheung, Sze-leung; Simpemba, Prospery C.; Benkhaldoun, Zouhair; Aubé, Martin; Moumen, Ismael; Suleiman, Raid M.; Czart, Krzysztof; Brudziński, Tomasz; Grochowalski, Paweł; Nowak, Agnieszka; Pałka, Dawid; Pęcek, Krzysztof; et al.
Abstract: Section 3 of the FM14 focus on the The IAU National Outreach Contacts (NOC) Network. This paper also contains supplementary materials that point to poster presentations that can be found online.